Semiotic Analysis of Cultural Da’wah: Decoding Religious Symbols and Public Reception in the Pepe’-pepeka ri Makka Dance of Makassar - Murdifin, Murdifin; Masry, Abd. Rasyid; Anshar, Muhammad; AB, Syamsuddin; Mirwan, Mirwan; Riswandi, Riswandi (Journal of Research and Multidisciplinary, 2025)
This research investigates the construction of religious messages and the efficacy of cultural preaching (da’wah) within the Pepe’-pepeka ri Makka (Fire in Mecca) dance tradition in Paropo Village, Makassar. While traditionally viewed as a cultural spectacle, this dance functions as a sophisticated medium for Islamic proselytization. Employing a qualitative descriptive method, this study utilizes Charles Sanders Peirce’s semiotic framework—comprising signs, objects, and interpretants—to analyze the ritual’s poetry and choreography. Data were collected through participatory observation, documentation, and in-depth interviews with key informants, including traditional maestros and religious figures. The findings reveal that the dance is a complex symbolic system representing core Islamic tenets, specifically Tawhid (monotheism), angelic hierarchies, and Thaharah (ritual purification). The fire serves as a potent index of divine light (Nur) and a symbol of spiritual resilience, echoing the miracle of Prophet Abraham. However, the analysis through the Stimulus-Organism-Response (SOR) model indicates a significant gap in public reception. While the performance elicits strong affective responses, such as awe and emotional engagement, the cognitive and behavioral impacts remain limited. This disconnect is attributed to linguistic barriers in the classical Makassarese poetry and the lack of explicit narrative interpretation. The study concludes that for cultural da’wah to achieve its transformative potential, "intersemiotic translation" is required to bridge the gap between traditional symbolism and contemporary public understanding.